Risk factors for bronchoscopic complications in patients over 75 years of age - TUFAN ÇİNÇİN, ASLI; KOCAKAYA, DERYA; ARIKAN, HÜSEYİN; OLGUN YILDIZELİ, ŞEHNAZ (ELSEVIER MASSON, CORPORATION OFFICE, 2018)
Aim Bronchoscopy is a widely used, well-tolerated diagnostic and therapeutic intervention and has a low complication rate. The aim of this study was to describe the rates of bronchoscopic complications and risk factors in a group of patients 75 years' old and above. Methods To investigate the rate of complications and risk factors in the older patients, we carried out a retrospective cohort study of 240 patients above 75 years of age who had bronchoscopy for various reasons. Results Complication rate was found to be 3.7% in the older patients group which was not different from the control group (1.2%, p > 0.05). No significant relationship was found between age group and complication development (p > 0.05). The type of procedures did not show any effect on complication development between age groups and individually. We found that anemia (OR 7.2, 95% CI 1.2-41.2), percutaneous gastrostomy (OR 9.9, 95% CI 1.6-58), immobility (OR 11.9, 95% CI 2.6-33.5) and procedures performed in the intensive care unit (OR 7.4, 95% CI 1.4-37.5) were significant risk factors for complication. Conclusions In the older patients group, bronchoscopy is a safe procedure regardless of the type of procedures performed and age. It has been shown that anemia, PEG presence, immobility and intensive care patients are associated with increased complication.
Keywords: Bronchoscopy; Complication; Older patients; Risk factor; FIBEROPTIC BRONCHOSCOPY; EXPERIENCE; FRAILTY